Nilai Edukatif Dalam Film Dua Garis Biru Karya Gina S. Noer - Sintya Putri Wulandari; Albertus Purwaka; Patrisia Cuesdeyeni; Linggua Sanjaya Usop; Alifiah Nurachmana (Universitas Palangka Raya, 2023)
The purpose of this study is to describe the representation of social values ​​in the sack. The problem explored in this research is social values ​​in the form of spiritual values ​​which include (1) truth values (2) honesty values (3) toughness values (4) caring values. The method and approach used in this research is a qualitative descriptive approach. Qualitative descriptive approach is used to describe the education values ​​in the film Dua Garis Biru by Gina S. Noer. Data analysis of this research was carried out by collecting data with the method of observing and recording, identifying data, classifying data, and describing data. The results of this study indicate that the educational values ​​contained in the film Dua Garis Biru by Gina S. Noer with several forms of value are as follows: (a) the educational value of honesty in the film is the most dominant, there are 15 forms of the value of honesty. (b) the educational value of toughness in the film shows 15 forms of toughness value. (c) the educational value of caring in the film shows 13 forms of caring value. (d) religious educational values ​​in the film show 8 forms of religious values.